PEMBERDAYAAN MASYARAKAT MELALUI SOSIALISASI DAN PENDAMPINGAN PADA PELAKU UMKM DI KELURAHAN KEPUH CIWANDAN - Fatari, Fatari; Sari, Nur Indah; Khaerunisa, Ratu Nazwa; Maulana, Rizki; Danik, Sadam Ahmad; Pasassung, Rendi; Nurlela, Siti Sarah; Ramadhan, Triana (Yayasan Education and Social Center, 2024)
This Community Service aims to provide outreach and assistance to the community of MSME actors in the Kepuh sub-district, Ciwandan sub-district, Cilegon city, so that MSME actors can understand management aspects, marketing aspects and financial aspects. The implementation method for community empowerment is by carrying out socialization and mentoring activities for MSME actors in the Kepuh sub-district, starting from identifying MSME actors and types of MSME products, determining the place and time to carry out activities. The result of this socialization and mentoring is that MSME players can understand and understand the material that has been presented, namely understanding management aspects, understanding marketing and understanding about running a business through MSMEs properly and correctly. The conclusion is that the assistance and outreach that has been carried out can help and the benefits can be felt by MSMEs in the Kepuh sub-district